Robots And Racism - Bartneck, Christoph; Yogeeswaran, Kumar; Ser, Qi Min; Woodward, Graeme; Sparrow, Robert; Wang, Siheng; Eyssel, Friederike (2018 13th ACM/IEEE International Conference on Human-Robot Interaction (HRI), 2018)
Most robots currently being sold or developed are either stylized with white material or have a metallic appearance. In this research we used the shooter bias paradigm and several questionnaires to investigate if people automatically identify robots as being racialized, such that we might say that some robots are 'White' while others are 'Asian', or 'Black'. To do so, we conducted an extended replication of the classic social psychological shooter bias paradigm using robot stimuli to explore whether effects known from human-human intergroup experiments would generalize to robots that were racialized as Black and White. Reaction-time based measures revealed that participants demonstrated 'shooter-bias' toward both Black people and robot racialized as Black. Participants were also willing to attribute a race to the robots depending on their racialization and demonstrated a high degree of inter-subject agreement when it came to these attributions.